A research note exploring firm action announcements and consumer attributions of blame: The moderating role of base‐rate information. (20th August 2019) - Yuan, Zhimei; Guo, Yi; Wang, Xingdong
Abstract: Consumer attributions of negative events have significant implications for crisis communication. This paper employs a scenario‐based between‐subjects design experiment to examine the effects of two types of action announcement, technical and ceremonial, on consumer attributions under different base‐rate conditions (crisis frequency in category). The findings suggest that, under high base‐rate condition, technical action announcements lead to more controllability and stability attributions than ceremonial action announcements for uninvolved firms. Under low base‐rate condition, technical action announcements lead to more stability attributions than ceremonial action announcements for involved firms.